Fostering mental health and wellness in interprofessional healthcare teams: Designing solutions through the application of Appreciative Inquiry and systems thinking. - Pryor, Stacy; Phillips, Amelia; Serag-Bolos, Erini; Casanova, Jesse; Blocker, Shaterra; Aul, Karen; Menon, Usha (Journal of Interprofessional Care)
There are increasing concerns about the well-being of healthcare students and providers. We describe our university's innovative approach to mitigating poor well-being across multiple healthcare disciplines during an Interprofessional Education (IPE) Day. As part of IPE Day, university health faculty developed a competition where teams of students from health colleges and programs created a strategic vision for mental health and wellness in the workplace. Twelve teams participated (7–9 students/team; N = 95). To help with strategic vision, participants created Mind Maps and Rich Pictures using Appreciative Inquiry as a framework. Appreciative Inquiry is an evidence-based approach that emphasizes strengths rather than weaknesses to facilitate positive change at a systems level. Evaluations included "Shark Tank" judging and audience voting to determine the competition's winner. Findings demonstrated that themes developed across teams converged more than they diverged, showing consensus on the broad key factors, including communication, collaboration, and community. Our study highlighted the success of bringing students from multiple disciplines together to collaborate on creating solutions to improve workplace well-being, benefiting all healthcare professions.